2006
DOI: 10.1111/j.1475-4932.2006.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Finance and Growth: A Critical Survey*

Abstract: We present a survey of the finance-growth nexus that raises a number of qualifications to the standard interpretation. We investigate doubts regarding empirical consensus and we consider the prevalence of crosssection econometrics as dominant in shaping the present theoretical consensus. The core implications of many finance and growth theories are shown to be disconnected not only from their modern empirical counterparts, but also from the historical literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 42 publications
0
25
0
2
Order By: Relevance
“…Therefore, sometimes it is not beneficial to the poor. Aghion and Bolton (1997) [42], Lloyd-Ellis and Bernhardt (2000) [43], Ueda (2003, 2006) [44,45], Chakraborty and Ray (2007) [46] all verified this view. Galor and Zeira (1993) [47], Ravallion (1997Ravallion ( , 2001 [48] thought that when the effect of distributive inequality is sufficient to offset the poverty alleviation effect of economic growth, financial development will be adverse to poverty alleviation.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 84%
“…Therefore, sometimes it is not beneficial to the poor. Aghion and Bolton (1997) [42], Lloyd-Ellis and Bernhardt (2000) [43], Ueda (2003, 2006) [44,45], Chakraborty and Ray (2007) [46] all verified this view. Galor and Zeira (1993) [47], Ravallion (1997Ravallion ( , 2001 [48] thought that when the effect of distributive inequality is sufficient to offset the poverty alleviation effect of economic growth, financial development will be adverse to poverty alleviation.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 84%
“…Development economics studies two types of relationships: first, the link between banking sector development and economic growth (Christopoulos & Tsionas, 2004;Majid & Mahrizal, 2007;Menyah et al, 2014;Moshirian & Wu, 2012;Tang, 2005); and second, the link between stock market development and economic growth (Choong, Yusop, Law, & Venus, 2003;Khan, 2004;Levine, 1991;Singh, 1997). In a broad-spectrum, both banking sector development and stock market development are main forces that can bring about high economic growth in a country (Bilson, Brailsford, & Hooper, 2001;Castaneda, 2006;Fink, Haiss, & Vuksic, 2006;Garcia & Liu, 1999;Gjerde & Saettem, 1999;Kwon & Shin, 1999;Nieuwerburgh, Buelens, & Cuyvers, 2006;Pagano, 1993;Schumpeter, 1911;Shan, Morris, & Sun, 2001;Shaw, 1973;Trew, 2006). It has been argued in a subset of the finance-growth literature that both banking sector development and stock market development can cause each other (Allen, Gu, & Kowalewski, 2012;Cheng, 2012;Gimet & Lagoarde-Segot, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies identified possible mechanisms through which financial liberalization promotes growth, including facilitating financial development, improving allocative efficiency, inducing technological progress and enhancing financial stability (Shaw, 1973;Levine, Loayza and Beck, 2000). Many empirical analyses also confirmed this positive correlation (Levine, 2005;Trew, 2006). Some other studies, however, cast doubts on this relationship.…”
Section: Introductionmentioning
confidence: 99%